Physical Education Learning Needs Across School Levels in Rural Golewa District Public Schools - Bate, Nikodemus; Wani, Bernabas; Laksana, Dek Ngurah Laba; Gae, Visensius Kea (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
This study examined the learning needs of Physical Education, Sports, and Health (PJOK) across elementary, junior high, and senior high public schools in Golewa District, Ngada Regency, Indonesia. The study used a descriptive survey with embedded qualitative interviews to capture both the measurable condition of PJOK implementation and teachers’ contextual experiences. The participants were nine PJOK teachers selected through total sampling from nine public schools, comprising three elementary schools, three junior high schools, and three senior high schools. Quantitative data were collected using a 24-item questionnaire on a four-point Likert scale covering teacher competence, facilities and infrastructure, learning tools, and school management support; qualitative data were gathered through semi-structured interviews. The instrument demonstrated acceptable content validity through expert judgment and satisfactory internal consistency for school-based needs mapping. Descriptive statistics were used to calculate mean scores, while interview transcripts were analysed thematically. The results indicated that the overall level of PJOK learning need remained moderate at all three educational levels, with mean scores of 2.83 in elementary schools, 2.80 in junior high schools, and 2.64 in senior high schools. The most pressing need at the elementary level was teacher competence (M = 2.27), whereas the sharpest gap at the senior high school level concerned curriculum-based learning tools (M = 1.53). Interview findings reinforced these patterns by showing recurring concerns about limited professional development, uneven equipment maintenance, and insufficient instructional documents. The study concludes that improving PJOK in rural schools requires level-sensitive interventions that combine teacher development, better instructional resources, and stronger managerial support.